Дослідження та програмна реалізація системи проектування сервісів автентифікації - Середа, Максим Леонідович; Sereda, Maxim (ЦНТУ, 2022)
В даній випускній кваліфікаційній роботі за другим (магістерським) рівнем вищої освіти розроблено програмне забезпечення, яке призначено для системи проектування сервісів автентифікації. Метою розробки є дослідження та програмна реалізація системи проектування сервісів автентифікації. Об’єктом дослідження є процес проектування сервісів автентифікації. Предметом дослідження є методи проектування сервісів автентифікації. Методи дослідження базуються на методах захисту інформації, методах математичної статистики, методах розробки програмного забезпечення. Результат роботи – програмна реалізація системи проектування сервісів автентифікації. В процесі роботи над програмною моделлю виконано аналіз існуючих апаратних та програмних засобів. В повній мірі описані всі компоненти розробленого програмного забезпечення. Розроблено зручний інтерфейс користувача. Наведені інструкції по роботі з програмними засобами. Програма може використовуватися на ПЕОМ архітектури IBM PC з ОС Windows 10/11. Програму розроблено в середовищі Delphi 10.4.1.In this graduation thesis for the second (master's) level of higher education, software is developed, which is intended for the design system of authentication services. The purpose of the development is research and software implementation of the design system of authentication services. The object of research is the process of designing authentication services. The subject of research is methods of designing authentication services. Research methods are based on information protection methods, mathematical statistics methods, and software development methods. The result of the work is the software implementation of the authentication service design system. In the process of working on the software model, an analysis of existing hardware and software was performed. All components of the developed software are fully described. A convenient user interface has been developed. Instructions for working with software tools are provided. The program can be used on PCs of IBM PC architecture with Windows 10/11 OS. The program was developed in the Delphi 10.4.1 environment.
Research and software implementation of the design system of authentication services
Keywords: комп’ютерна інженерія; автентифікація; computer engineering; authentication